2015
DOI: 10.1016/j.msec.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Surface engineering of a Zr-based bulk metallic glass with low energy Ar- or Ca-ion implantation

Abstract: In the present study, low energy ion implantation was employed to engineer the surface of a Zr-based bulk metallic glass (BMG), aiming at improving the biocompatibility and imparting bioactivity to the surface. Ca- or Ar-ions were implanted at 10 or 50 keV at a fluence of 8 × 10(15)ions/cm(2) to (Zr0.55Al0.10Ni0.05Cu0.30)99Y1 (at.%) BMG. The effects of ion implantation on material properties and subsequent cellular responses were investigated. Both Ar- and Ca-ion implantations were suggested to induce atom dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…An earlier study has demonstrated the high MRI compatibility of BMGs . Besides, BMGs are easily amenable for surface modification and functionalization . A recent study has reported fatigue analysis of a balloon expandable vascular stent subjected to pulsatile loading and the results showed that the BMG stent could withstand pulsatile pressure from the vessel wall .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier study has demonstrated the high MRI compatibility of BMGs . Besides, BMGs are easily amenable for surface modification and functionalization . A recent study has reported fatigue analysis of a balloon expandable vascular stent subjected to pulsatile loading and the results showed that the BMG stent could withstand pulsatile pressure from the vessel wall .…”
Section: Introductionmentioning
confidence: 99%
“…35 Besides, BMGs are easily amenable for surface modification and functionalization. 36,37 A recent study has reported fatigue analysis of a balloon expandable vascular stent subjected to pulsatile loading and the results showed that the BMG stent could withstand pulsatile pressure from the vessel wall. 38 However, in general, BMGs suffer from lack of ductility, and there is an inherent risk of catastrophic failure near room temperature due to highly localized plastic deformation especially after yielding.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the success of conventional polycrystalline biometals as stent material, the emergence of BMGs has opened new horizons for development of competitive alternatives for different stent applications . The functional properties and biocompatibility of a prototypical Zr-based BMG to be used as stent material have been extensively investigated, and it is confirmed that this class of materials offers better biocompatibility than conventional crystalline alloys in both vitro cell culture and in vivo animal implantations. ,, The high corrosion resistance of Zr-based BMGs is due to the passive films primarily composed of ZrO2 that are formed on the alloy’s outer surface. , On the other hand, the high strength of the BMGs greatly enables the production of stents with thinner struts, which contributes to its ease of delivery and reduces the rate of restenosis. For example, in comparison to traditional 316L stainless steel stents, Zr-based BMG stents would require just one-third of the strut cross-section and yet provide in excess of five times the strength .…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study has demonstrated that Zr-based BMGs exhibited a definitive shape as compared to the distorted configuration of a Cu-4Cr-2Nb (weight percent) crystalline alloy under MRI [25]. Moreover, BMGs are easily amenable for surface modification and functionalization [26,27]. However, to the best of the authors' knowledge, the capability and biocompatibility of BMGs in the context of potential stent materials remain unexplored.…”
Section: Introductionmentioning
confidence: 99%